The unity of virtue revisited: A resolution to a Socratic enigma. - Vaughan, Barry Frank. (My University, 1999)
Socrates' assertions about the relationship between the cardinal virtues of justice, temperance, piety, courage, and wisdom have long been a source of controversy among scholars. While it is generally held that his position can be described as suggesting a unity among the virtues, the precise nature of this unity is debated. In this dissertation I argue that throughout the early dialogues Socrates is committed to the position that the various virtue terms are merely different names for virtue proper. I further argue that according to this view Socrates is committed to a position which entails that the virtue terms are synonymous with one another. I develop my argument by responding to four major alternative interpretations of Socrates' doctrine of virtue.
Keywords: Socrates Contributions in doctrine of virtue.; Philosophy.